Cross-disciplinary advances in applied natural language processing issues and approaches - Boonthum-Denecke, Chutima, 1976-.; McCarthy, Philip M., 1967-.; Lamkin, Travis A., 1979-.; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
'Applied Natural Language Processing (ANLP) is interested in not only the creation of natural language processing approaches (i.e., tools, systems, algorithms, models, theories, and techniques), but it is also (and, arguably, more specifically) interested in how those approaches stack up against new problems, issues, identified knowledge gaps, or created data sets. Cross-Disciplinary Advances in Applied Natural Language Processing: Issues and Approaches defines the role of ANLP within NLP, and alongside other disciplines such as linguistics, computer science, and cognitive science. The description also includes the categorization of current ANLP research, and examples of current research in ANLP. This book is a useful reference for teachers, students, and materials developers in fields spanning linguistics, computer science, and cognitive science'--Provided by publisher.
1. Computational semantics requires computation / Yorick Wilks -- 2. Natural language processing tools / Chutima Boonthum-Denecke, Justin F. Brunelle -- 3. Information extraction from text and beyond / Marie-Francine Moens -- 4. Corpora and concordancers / Charles Hall -- 5. Lexical challenges in the intersection of applied linguistics and ANLP / Scott Jarvis -- 6. The user-language paraphrase corpus / Danielle S. McNamara, Philip M. McCarthy -- 7. Amazon Mechanical Turk: a web-based tool for facilitating experimental research in ANLP / Amber Chauncey Strain, Lucille M. Booker -- 8. Some issues on capturing the meaning of negated statements / Eduardo Blanco, Dan Moldovan -- 9. Cognitive load aspects of text processing / Slava Kalyuga -- 10. Understanding and reasoning with text / Joseph P. Magliano ... [et al.] -- 11. Guru: designing a conversational expert intelligent tutoring system / Andrew M. Olney, Natalie K. Person, Arthur C. Graesser -- 12. P-MATCH: identifying part name in noisy text data / Anne Kao ... [et al.] -- 13. Disambiguation and filtering methods in using web knowledge for coreference resolution / Olga Uryupina ... [et al.] -- 14. Newness and givenness of information: automated identification in written discourse / Danielle S. McNamara ... [et al.] -- 15. Improving spoken dialogue understanding using phonetic mixture models / William Yang Wang ... [et al.] -- 16. Mining and visualizing the narration tree of Hadiths (prophetic traditions) / Aqil Azmi, Nawaf AlBadia -- 17. Combinatory categorial grammar for computer-assisted language learning / Simon Delamarre, Maryvonne Abraham -- 18. Fairy tales and ESL texts: an analysis of linguistic features using the Gramulator / Travis Lamkin, Philip M. McCarthy, Rachel M. Rufenacht -- 19. Text-based affect detection in intelligent tutors / Arthur C. Graesser, Sidney D'Mello -- 20. Multiple influences on the use of English Spatial prepositions: the case of'in' and'on' / Michele I. Feist, Dedre Gentner -- 21. Evaluating semantic metrics on tasks of concept similarity / Hansen A. Schwartz, Fernando Gomez -- 22. Extracting commonsense knowledge using concepts properties / Eduardo Blanco, Dan Moldovan, Hakki C. Cankaya -- 23. Co-occurrence-based error correction approach to word segmentation / Ekawat Chaowicharat, Kanlaya Naruedomkul.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed March 20, 2012).
Keywords: Natural language processing (Computer science).; ANLP applications; Applied linguistics; Artificial intelligence; Cognitive science; Computational linguistics; Content analysis; Human computer interaction; Language engineering; Natural language processing; Semantic analysis